Cubed Square Roots

Algebra Level 1

Simplify

( 2 + 3 ) 3 + ( 2 3 ) 3 . ( 2 + \sqrt{3})^3 + ( 2 - \sqrt{3})^3.


The answer is 52.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Arron Kau Staff
May 13, 2014

Solution 1: Factoring the sum of cubes, we have

( 2 + 3 ) 3 + ( 2 3 ) 3 = ( ( 2 + 3 ) + ( 2 3 ) ) ( ( 2 + 3 ) 2 ( 2 + 3 ) ( 2 3 ) + ( 2 3 ) 2 ) = ( 4 ) ( ( 4 + 4 3 + 3 ) ( 4 3 ) + ( 4 4 3 + 3 ) ) = ( 4 ) ( 13 ) = 52 \begin{aligned} (2 + \sqrt{3})^3 + (2 - \sqrt{3})^3 &= \left((2 + \sqrt{3}) + (2 - \sqrt{3})\right)\left((2 + \sqrt{3})^2 - (2 + \sqrt{3})(2 - \sqrt{3}) + (2 - \sqrt{3})^2\right) \\ &= (4)\left((4 + 4\sqrt{3} + 3) -(4 - 3) + (4 - 4\sqrt{3} + 3) \right) \\ &= (4)(13) \\ &= 52 \\ \end{aligned}

Solution 2: ( 2 + 3 ) 3 = ( 2 + 3 ) 2 × ( 2 + 3 ) = ( 4 + 2 2 3 + 3 ) × ( 2 + 3 ) = ( 7 + 4 3 ) ( 2 + 3 ) = 14 + 8 3 + 7 3 + 12 = 26 + 15 3 \begin{aligned} (2+\sqrt{3} ) ^3 &= ( 2 + \sqrt{3})^2 \times ( 2 + \sqrt{3} ) \\ &= ( 4 + 2 \cdot 2 \cdot \sqrt{3} + 3) \times ( 2 + \sqrt{3} ) \\ &= ( 7 + 4 \sqrt{3} ) (2 + \sqrt{3} ) \\ &= 14 + 8 \sqrt{3} + 7 \sqrt{3} +12 \\ &= 26 + 15 \sqrt{3} \\ \end{aligned}

Similarly,

( 2 3 ) 3 = ( 2 3 ) 2 × ( 2 3 ) = ( 4 2 2 3 + 3 ) × ( 2 3 ) = ( 7 4 3 ) ( 2 3 ) = 14 8 3 7 3 + 12 = 26 15 3 \begin{aligned} (2-\sqrt{3} ) ^3 &= ( 2 - \sqrt{3})^2 \times ( 2 - \sqrt{3} ) \\ &= ( 4 - 2 \cdot 2 \cdot \sqrt{3} + 3) \times ( 2 - \sqrt{3} ) \\ &= ( 7 - 4 \sqrt{3} ) (2 - \sqrt{3} ) \\ &= 14 - 8 \sqrt{3} - 7 \sqrt{3} +12 \\ &= 26 - 15 \sqrt{3} \\ \end{aligned}

Hence, ( 2 + 3 ) 3 + ( 2 3 ) 3 = ( 26 + 15 3 ) + ( 26 15 3 ) = 52 ( 2 + \sqrt{3})^3 + ( 2 - \sqrt{3})^3 = (26 + 15 \sqrt{3} ) + (26 - 15 \sqrt{3}) = 52 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...